Evolutionary Biology: Exobiology and Evolutionary Mechanisms - Pontarotti, Pierre (Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book presents 19 selected contributions to the 16th Evolutionary Biology Meeting, which took place in September 2012 in Marseilles. The aims of these annual meetings, which gather together leading evolutionary bioloigsts and other sienctists, are to promote the exchange of ideas and to encourage interdisciplinary collaborations. The first chapter deals with the history of a great discovery: The first experiments on ascidian and sea urchin egg fertilization. The remaining contributions are grouped under the following categories: · Evolutionary biology concepts · Exobiology and the origin of life · Evolutionary mechanisms Offering an up-to-date overview of recent findings in the field of evolutionary biology, this book is an invaluable source of information for scientists, teachers and advanced students.